Masalah Pelajar dalam Menamakan Sebatian-Sebatian Organik Berpolifungsi - Mohd Nor, Rehan (1991)
An investigation of students' unsuccessful attempts in naming poly functional organic compounds using the IUPAC nomenclature is described, The effectiveness of the teaching strategies used to help students develop skill and confidence in using the systematic nomenclature is also discussed.